Conductive paste, electrode, electronic component, and electronic device
By using the conductive paste of the palladium compound surface treatment layer in the conductive particles, the problem of wire breakage caused by vulcanization in the prior art is solved, and a conductive paste with high vulcanization resistance and low cost is achieved.
Patent Information
- Application Number
- CN202380056819.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-26
- Filing Date
- 2023-07-04
- Publication Date
- 2025-02-28
AI Technical Summary
When the existing conductive paste improves low resistance, high printing and adhesiveness, it is difficult to simultaneously suppress the disconnection problem caused by vulcanization, and using palladium as a surface treatment agent increases costs.
A conductive paste containing conductive particles and a binder resin is used, wherein the conductive particles have metal particles and a palladium compound surface treatment layer disposed on the surface of the metal particles. The conductive particles content is 80 parts by weight or more, and the palladium compound content contained in the surface treatment layer is between 0.01 and 1.0 parts by weight.
High vulcanization resistance and excellent printing characteristics are achieved, and good printing characteristics can be maintained even if the content of conductive particles is increased, and the cost is reduced.
Smart Images

Figure CN119547160A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive paste used for forming an electrode of an electronic component, for example, and also to an electrode formed using the conductive paste, and an electronic component such as a chip resistor having the electrode. Background Art
[0002] In forming the electrodes of a chip resistor, which is a type of electronic component, a conductive paste containing silver powder (silver particles) is used. Figure 1 An example of a cross-sectional structure of a chip resistor 100 is shown in FIG. 1 . The chip resistor 100 has a rectangular alumina substrate 102, and a resistor 104 and a lead electrode 106 for leading electricity from the resistor 104 are formed on the upper surface of the alumina substrate 102. In addition, a lower surface electrode 108 for mounting the chip resistor 100 on the substrate is formed on the lower surface of the alumina substrate 102. In addition, a connecting electrode 110 for connecting the lead electrode 106 to the lower surface electrode 108 is formed on the end surface of the alumina substrate 102. The lead electrode 106 and the lower surface electrode 108 are formed by applying a conductive paste on the upper surface and the lower surface of the alumina substrate 102 by printing and then firing. A nickel plating film 112 and a tin plating film 114 are usually formed on the lead electrode 106, the lower surface electrode 108, and the connecting electrode 110.
[0003] As a conductive paste used for forming an electrode, Patent Document 1 discloses a paste for a chip resistor upper surface electrode in which conductive powder, glass powder, and an inorganic binder are dispersed in an organic vehicle.
[0004] Patent Document 2 discloses a conductive paste comprising (A) surface-treated metal particles containing Ag and Sn, (C) glass powder, and (B) a binder resin, wherein the weight ratio of Sn in the (A) conductive particles is less than 10 weight %.
[0005] With the recent improvement in the performance of electronic devices and electronic components, further lower resistance is required for electrodes, wiring, etc. As one of the methods to reduce the resistivity, a method of setting the conductive particles to be highly filled has been implemented. For example, in Patent Document 3, a conductive paste containing silver powder at a high ratio of 85 parts by weight or more is disclosed. On the other hand, the conductor patterns that become electrodes, wiring, etc. tend to be highly refined and complicated with the improvement in the performance of electronic devices and electronic components. Therefore, the conductive paste is required to have adhesion for fixing to the substrate and excellent printing properties that can form fine patterns, such as leveling for forming a smooth coating film during coating, and smoothness of the coating film for further plating the coated area. Patent Document 3 discloses that if the silver powder is greater than 95 parts by weight relative to a total of 100 parts by weight of the silver powder and the binder resin, the printability and adhesion are affected.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 7-335402
[0009] Patent Document 2: International Publication No. 2021 / 145269
[0010] Patent Document 3: Japanese Patent Application Publication No. 2005-294254 Summary of the invention
[0011] Problems to be solved by the invention
[0012] The low resistance, high printability, and high adhesion of conductive pastes are all required properties as electronic devices advance, but sometimes there is a trade-off between the two, and there is a demand for conductive pastes that excel in either performance. In addition to low resistance, high printability, and high adhesion, there are also properties required for highly refined electronic devices.
[0013] In gasoline vehicles and thermal power plants, sulfur oxides are discharged into the atmosphere in large quantities by burning fossil fuels. In addition, in sewage treatment plants and garbage disposal sites, sulfur is reduced by anaerobic bacteria to produce hydrogen sulfide. Therefore, sulfur-containing components such as sulfur oxides and hydrogen sulfide exist in the atmosphere.
[0014] If the sulfur-containing components in the atmosphere reach the surface of metals such as silver, the sulfur components will adhere to the surface of metals such as silver, react with metals such as silver, and become metal sulfides such as silver sulfide. For example, the same reaction occurs in electrodes such as electrodes of chip resistors that use silver as the main material, so there are cases where silver and other metals inside the electrode become metal sulfides such as silver sulfide. If metal sulfides such as silver sulfide are generated inside the electrode, the electrode may be disconnected. Therefore, in devices such as chip resistors that have electrodes made of metals such as silver, malfunctions sometimes occur. Such a phenomenon is called disconnection due to sulfidation. In addition to silver, disconnection due to sulfidation may also occur in electrodes of copper, indium, aluminum, and alloys containing at least one of them.
[0015] If the metal particles are filled to a high level, the degree of sulfurization reaction will increase accordingly, so it is required to be able to suppress disconnection due to sulfurization even if the conductive paste has a low resistance. In order to suppress disconnection due to sulfurization, electrodes made of metals such as silver as the main material used in devices such as chip resistors need to have high sulfurization resistance.
[0016] As conductive particles of a conductive paste for forming an electrode with high sulfidation resistance, it has been proposed to use palladium alone or to add a predetermined amount (e.g., about 20% by weight) of palladium. However, since palladium is expensive, the cost of the conductive paste increases by using palladium alone or adding palladium, which leads to a problem of increasing the cost of the electrode.
[0017] Therefore, an object of the present invention is to provide a conductive paste having high sulfurization resistance and capable of achieving excellent printing characteristics even when the content of conductive particles is further increased.
[0018] Means for solving problems
[0019] In order to solve the above-mentioned problems, the present invention has the following configurations.
[0020] (Composition 1)
[0021] Configuration 1 is a conductive paste comprising (A) conductive particles and (B) a binder resin, wherein the conductive particles (A) have metal particles and a surface treatment layer comprising a palladium compound disposed on at least a portion of a surface of the metal particles, and the conductive particles (A) are contained in an amount of 80 parts by weight or more relative to 100 parts by weight of the conductive paste.
[0022] (Composition 2)
[0023] Configuration 2 is the conductive paste of Configuration 1, wherein the viscosity measured by an HB type viscometer at 25° C. and 10 rpm is in the range of 50 to 700 Pa·s.
[0024] (Composition 3)
[0025] Configuration 3 is the conductive paste of Configuration 1 or 2, wherein the thixotropic index value (TI) which is a ratio of the viscosity at a rotation speed of 1 rpm to the viscosity at a rotation speed of 10 rpm measured at 25° C. using an HB type viscometer is 2.5 or less.
[0026] (Composition 4)
[0027] Configuration 4 is the conductive paste according to any one of Configurations 1 to 3, wherein the average particle size (D50) of the (A) conductive particles is 0.1 to 10 μm.
[0028] (Composition 5)
[0029] Configuration 5 is the conductive paste according to any one of Configurations 1 to 4, wherein the metal particles contain 50 wt % or more of silver.
[0030] (Composition 6)
[0031] Configuration 6 is the conductive paste according to any one of Configurations 1 to 5, wherein the content of the palladium compound contained in the surface treatment layer is 0.01 to 1.0 part by weight based on 100 parts by weight of the conductive particles.
[0032] (Composition 7)
[0033] Configuration 7 is the conductive paste of Configuration 6, wherein the content of the palladium compound contained in the surface treatment layer is 0.2 to 0.4 parts by weight based on 100 parts by weight of the conductive particles.
[0034] (Composition 8)
[0035] Configuration 8 is the conductive paste according to any one of Configurations 1 to 7, wherein the surface treatment layer further contains an organic substance.
[0036] (Composition 9)
[0037] Configuration 9 is an electrode obtained by firing or heat-treating the conductive paste of any one of Configurations 1 to 8.
[0038] (Composition 10)
[0039] Configuration 10 is the electrode of Configuration 9, wherein the arithmetic mean roughness (Ra) of the electrode surface measured in accordance with JIS B 0601 (1994) is 0.5 μm or less.
[0040] (Composition 11)
[0041] Configuration 11 is an electronic component or electronic device including the electrode of configuration 9 or 10.
[0042] Effects of the Invention
[0043] According to the present invention, it is possible to provide a conductive paste which has high sulfurization resistance and can achieve excellent printing characteristics even if the content of the conductive particles is further increased. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a schematic diagram showing an example of the cross-sectional structure of a chip resistor.
[0045] Figure 2 It is a schematic diagram showing the shape of the test piece used for the sulfurization resistance test of the Example and the Comparative Example.
[0046] Figure 3 These are optical microscope photographs showing the shapes of test printed patterns of test pieces used in migration resistance tests of Examples and Comparative Examples.
[0047] Figure 4 Yes Figure 3 This is an optical micrograph of the enlarged center of the optical micrograph of the test printed pattern of the test piece used in the migration resistance test.
[0048] Figure 5 This is a scanning electron microscope (SEM) photograph (magnification 5000 times) of the surface of a fired body of the conductive paste after a test piece produced under the same conditions as in Example 3 was stored in a sulfur-containing gas atmosphere for 150 hours to be vulcanized.
[0049] Figure 6 This is a scanning electron microscope (SEM) photograph (magnification 5000 times) of the surface of a fired body of the conductive paste after a test piece produced under the same conditions as in Comparative Example 1 was stored in a sulfur-containing gas atmosphere for 150 hours to be vulcanized.
[0050] Figure 7 This is a graph showing the time change of the insulation resistance value of Example 1, Example 3, and Comparative Example 1 when the migration resistance test was performed.
[0051] Figure 8 This is a stereomicroscope photograph of a thin film using the conductive paste of Example 22.
[0052] Fig. 9 This is a stereomicroscope photograph of a thin film using the conductive paste of Comparative Example 6. DETAILED DESCRIPTION
[0053] Hereinafter, embodiments of the present invention will be described in detail. It should be noted that the following embodiments are only modes for embodying the present invention, and the present invention is not limited to the scope thereof.
[0054] The conductive paste of the present embodiment includes (A) conductive particles and (B) a binder resin. The conductive paste of the present embodiment can be preferably used to form electrodes of electronic components such as chip resistors. The conductive particles (A) have metal particles and a surface treatment layer including a palladium compound disposed on at least a portion of the surface of the metal particles, and are included in an amount of 80 parts by weight or more relative to 100 parts by weight of the conductive paste.
[0055] First, components contained in the conductive paste of this embodiment will be described.
[0056] <(A) Conductive particles>
[0057] The conductive paste of the present embodiment includes (A) conductive particles. The conductive particles (A) include metal particles and a surface treatment layer disposed on at least a portion of the surface of the metal particles. The surface treatment layer is a thin film containing a palladium compound. The metal particles are surface-treated with the palladium compound to form the surface treatment layer. By making the conductive particles (A) include surface-treated metal particles having a given surface treatment layer, sulfidation of the metal contained in the conductive particles can be suppressed. Therefore, by using the conductive paste of the present embodiment, an electrode with high sulfidation resistance can be formed.
[0058] It should be noted that the inventors of the present invention have found that by making the conductive particles (A) of the conductive paste of the present embodiment include a given surface treatment layer, the migration resistance of the obtained electrode is also improved as an additional effect. The so-called migration resistance means the property of being able to suppress migration. The so-called migration is a phenomenon in which, when a voltage is applied to a pair of electrodes (positive and negative electrodes), if there is water and / or water vapor near the electrodes, the metal contained in the electrodes and the wiring parts is ionized and moves from the positive electrode to the negative electrode, resulting in metal dendrites, and the insulation between the wiring parts is reduced. In addition, migration sometimes occurs in an atmosphere without the influence of moisture, such as above 100°C or in a vacuum. In this case, even if a pair of electrodes reaches a state close to a short circuit, there is no generation of dendrites between the wiring parts that is necessarily observed when migration occurs in the presence of moisture, and no polarity is observed (that is, it will occur regardless of the polarity of the positive and negative electrodes). The so-called migration resistance means the property of being able to suppress such migration that has been widely known. Due to the migration of the metal, a pair of electrodes may be short-circuited. By improving the migration resistance, the short circuit of the electrode can be suppressed. In addition, it was found that the migration resistance of the electrode obtained by the conductive paste of the present embodiment is improved not only in the case of the conductive paste of the type fired at a relatively high temperature (e.g., 500 to 900°C), but also in the case of the thermosetting conductive paste that is heat-cured by heat treatment at a relatively low temperature (e.g., 100 to 200°C). However, it is believed that the advantage of improved migration resistance is not necessarily a necessary effect of the conductive paste of the present embodiment, but is an advantage.
[0059] (A) The conductive particles may contain metals other than surface-treated metal particles. However, in order to reliably obtain an electrode with low resistance and high resistance to sulfidation, the conductive particles (A) preferably contain 50% by weight or more of surface-treated metal particles, more preferably 80% by weight or more of surface-treated metal particles, further preferably 90% by weight or more of surface-treated metal particles, and particularly preferably consist only of surface-treated metal particles. It should be noted that in this specification, the so-called "(A) conductive particles consist only of surface-treated metal particles" means that the conductive particles (A) are not intentionally combined with metals other than surface-treated metal particles, and the case of containing conductive particles other than surface-treated metal particles that are inevitably mixed is not excluded.
[0060] (A) The conductive particles may include metal particles of materials such as Zn, In, Al and / or Si as metal particles other than the surface-treated metal particles, within a range that does not impair the effects of the present embodiment. The metal particles contained in the surface-treated metal particles and the metal particles other than the surface-treated metal particles may be alloy metal particles. In addition, the metal particles contained in the surface-treated metal particles and the metal particles other than the surface-treated metal particles may include metal particles of multiple metals or alloys of different types.
[0061] The surface-treated metal particles include metal particles and a surface-treated layer disposed on at least a portion of the surface of the metal particles. The surface-treated layer is a thin film formed on at least a portion of the surface of the metal particles. The metal particles are surface-treated with a palladium compound, thereby forming a surface-treated layer on at least a portion of the surface of the metal particles. Thus, the surface-treated metal particles can be metal particles surface-treated with a palladium compound.
[0062] The material of the metal particles surface-treated with the palladium compound can be Ag, Cu, In, Al, or alloys thereof. From the viewpoint of high electrical conductivity, the material of the metal particles is preferably Ag and / or Cu, and more preferably Ag.
[0063] The conductive paste of the present embodiment preferably contains 50% by weight or more of silver (Ag) in the metal particles, more preferably 80% by weight or more of silver (Ag), further preferably 90% by weight or more of silver (Ag), and particularly preferably 95% by weight or more of silver (Ag). In the most preferred embodiment, the metal particles of the surface-treated metal particles contained in the conductive paste of the present embodiment are composed only of silver (Ag) particles. This is because the electrical conductivity of silver is higher than that of other metals. It should be noted that in this specification, the so-called "the metal particles of the surface-treated metal particles are composed only of silver (Ag) particles" means that metal particles other than silver (Ag) particles are not intentionally used as metal particles, and the case of containing metal particles other than silver (Ag) particles that are inevitably mixed is not excluded. The same description does not exclude the substances that are inevitably mixed.
[0064] The conductive paste of the present embodiment preferably contains 50 parts by weight or more of the surface-treated metal particles based on 100 parts by weight of the conductive paste, more preferably 70 parts by weight or more, and even more preferably 80 parts by weight or more.
[0065] The conductive paste of the present embodiment preferably contains 50 to 99 parts by weight of surface-treated metal particles, more preferably 70 to 97 parts by weight, and even more preferably 80 to 95 parts by weight, relative to 100 parts by weight of the conductive paste. By setting the content within the above range, an electrode having high sulfidation resistance and low cost can be formed.
[0066] The method for producing the metal particles is not particularly limited, and the metal particles may be produced by, for example, reduction, pulverization, electrolysis, atomization, heat treatment, or a combination thereof. The flaky metal particles may be produced by, for example, flattening spherical or granular metal particles using a ball mill or the like.
[0067] The surface-treated metal particles include a surface-treated layer disposed on at least a portion of the surface of the metal particles. The surface-treated layer is a thin film formed on at least a portion of the surface of the metal particles by surface-treating the metal particles with a surface-treating agent containing a palladium compound.
[0068] As the palladium compound used as a raw material for surface treatment of metal particles, at least one selected from palladium complexes such as palladium chloride (II), palladium oxide (II), an organic palladium compound, palladium fluoride, palladium carbon, n-allyl palladium complex, cyclopentadienyl allyl palladium, bis(triphenylphosphine) palladium dichloride (II), palladium bromide, and a fatty acid complex of palladium such as palladium oleate can be used. As the palladium compound used as a raw material for surface treatment of metal particles, palladium chloride is preferably used.
[0069] The surface treatment layer can be formed by surface treatment using a palladium compound using a known method. Specifically, the surface treatment layer is a layer obtained by attaching a palladium soap solvent (surface treatment agent) containing palladium or palladium ions, organic matter and solvents for dispersing them to the surface of metal particles, and removing the solvent using a drying process. Thus, a surface treatment layer containing a palladium compound can be formed on the surface of the metal particles. It should be noted that although there is also a technology for coating other metal particles on the surface of metal particles using reduction treatment to form a core-shell structure, when attempting to use this technology to form a surface treatment layer, in order to precipitate a shell (such as palladium metal particles) on the surface of the core particles (such as silver particles), the amount of palladium metal particles in the shell becomes more. That is, the amount of palladium used becomes more. On the other hand, in the present invention, since the surface treatment layer is formed in a state where the palladium compound is attached to the surface of the metal particles, there is an effect that the amount of palladium used can be a small amount. Palladium is an expensive metal due to its rarity and partiality. From the perspective of cost, it is extremely important to have excellent sulfidation resistance and printing characteristics even in a small amount.
[0070] As the organic substance for dispersing palladium or palladium ions, at least one selected from fatty acids and triazole compounds is preferred. In the case of using fatty acids as solvents, as fatty acids, at least one selected from butyric acid, valeric acid, caproic acid, heptanoic acid, caprylic acid, nonanoic acid, capric acid, lauric acid, myristic acid, pentadecanoic acid, palmitic acid, palmitoleic acid, heptadecanoic acid, stearic acid, oleic acid, vaccenic acid, linoleic acid, linolenic acid, eicosanoic acid, eicosadienoic acid, eicosatrienoic acid, eicosatetraenoic acid, arachidonic acid, behenic acid, lignoceric acid, nervonic acid, cerotic acid, montanic acid and melissic acid can be used. Among these fatty acids, at least one selected from palmitic acid, stearic acid and oleic acid is preferably used. As the organic substance (fatty acid) contained in the surface treatment agent, oleic acid is more preferably used. In the case of using triazole compounds as organic substances for dispersing palladium or palladium ions, benzotriazole can be used as the triazole compound.
[0071] It should be noted that the solvent contained in the surface treatment agent for forming the surface treatment layer can be any solvent as long as it is used to disperse palladium or palladium ions and to make the palladium compound adhere well to the metal particles. Examples of the solvent include alcohols such as methanol, ethanol, and isopropyl alcohol (IPA), organic acids such as ethylene acetate, aromatic hydrocarbons such as toluene and xylene, N-alkylpyrrolidones such as N-methyl-2-pyrrolidone (NMP), amides such as N,N-dimethylformamide (DMF), ketones such as methyl ethyl ketone (MEK), cyclic carbonates such as terpineol (TEL) and diethylene glycol monobutyl ether (butyl carbitol, BC), bis[2-(2-butoxyethoxy)ethyl]adipate, 2,2,4-trimethylpentane-1,3-diol monoisobutyrate (TEXANOL), and water.
[0072] The surface treatment agent containing the solvent in which the palladium compound is dispersed is attached to the surface of the metal particles, and the solvent is removed by drying, thereby forming a surface treatment layer on the surface of the metal particles. In this way, surface-treated metal particles can be obtained.
[0073] In addition, the surface treatment layer of the surface-treated metal particles can be manufactured as follows. That is, first, the metal particles are dispersed in water. In the water in which the metal particles are dispersed, the above-mentioned solvent dispersed with the palladium compound is added as a coating agent, and after obtaining a water slurry containing metal particles coated with a coating agent containing palladium, the metal particles coated with the coating agent are precipitated by decantation. Then, the supernatant is removed, and the obtained wet metal particles coated with the coating agent are added to a polar solvent with a boiling point of 150 to 300°C together with an acrylic dispersant. Thereafter, the surface-treated metal particles can be manufactured by drying for more than 12 hours at a temperature of room temperature to 100°C, preferably at a temperature below 80°C, in a nitrogen atmosphere to remove moisture. It should be noted that if the drying temperature is too high, the surface-treated metal particles will sinter, so it is not preferred.
[0074] The surface treatment layer of the surface-treated metal particles contained in the conductive paste of the present embodiment preferably further comprises an organic substance. For example, when the surface treatment layer is formed using the above-mentioned palladium compound, the surface treatment layer will comprise an organic substance. By making the surface-treated metal particles have a surface treatment layer comprising an organic substance, even if the amount of the palladium compound is a small amount, the resulting electrode can have high resistance to sulfidation. It should be noted that the organic substance can be a liquid organic fatty acid or a solid fatty acid. As examples of liquid fatty acids, saturated fatty acids such as butyric acid, valeric acid, caproic acid, heptanoic acid, octanoic acid and nonanoic acid, and unsaturated fatty acids such as myristic acid, palmitoleic acid, ricinoleic acid, oleic acid, linoleic acid and linolenic acid can be cited. These fatty acids can be used alone or in combination of more than two. Among them, oleic acid, linoleic acid or a mixture thereof is preferably used. As examples of solid fatty acids, saturated fatty acids such as capric acid, palmitic acid and stearic acid with more than 10 carbon atoms, and unsaturated fatty acids such as crotonic acid and sorbic acid can be cited.
[0075] The surface treatment layer of the surface-treated metal particles used in the present embodiment is a thin film of a palladium compound. In the present embodiment, it is characterized in that the surface treatment layer of the surface-treated metal particles is not a thin film composed of palladium metal or a palladium alloy. In the case where the surface treatment layer is a thin film composed of palladium metal or a palladium alloy, due to the excessive amount of palladium, there are adverse effects such as an increase in the resistance of the resulting electrode. In addition, after sintering, due to the presence of a large amount of palladium metal or a palladium alloy on the surface of the metal particles, the wettability of the solder to metal particles such as silver particles deteriorates, and the possibility of soldering being hindered becomes higher. In addition, if the amount of palladium used increases, the cost will increase.
[0076] The surface treatment layer is a thin film formed on at least a portion of the surface of the metal particle. The surface treatment layer is preferably a thin film covering more than 50% of the surface of the metal particle, more preferably a thin film covering more than 80% of the surface of the metal particle, further preferably a thin film covering more than 90% of the surface of the metal particle, and particularly preferably a thin film covering more than 95% of the surface of the metal particle. The surface treatment layer is most preferably a thin film covering the entire surface of the metal particle.
[0077] The film thickness of the surface treatment layer of the surface-treated metal particles does not necessarily need to be uniform, but in order to more effectively suppress the sulfidation of the metal particles, it is preferably uniform. It should be noted that the control of the film thickness of the surface treatment layer can be controlled, for example, by adjusting the viscosity of the palladium soap solvent (surface treatment agent) in which the palladium compound is dispersed in the solvent and the concentration of the palladium compound in the palladium soap solvent (surface treatment agent). In addition, by controlling the film thickness of the surface treatment layer, the amount of palladium contained in the surface treatment layer can be controlled. It should be noted that the film thickness of the surface treatment layer is preferably less than 1 to 100 nm, more preferably less than 1 to 70 nm, and particularly preferably less than 1 to 50 nm. The thickness of the surface treatment layer can be measured, for example, by X-ray photoelectron spectroscopy. By setting the film thickness of the surface treatment layer to this range, an electrode with high sulfidation resistance can be formed while reducing the amount of palladium compound.
[0078] By including surface-treated metal particles that have been surface-treated with a palladium compound as (A) conductive particles in the conductive paste of this embodiment, an electrode having high sulfidation resistance can be formed without using a large amount of expensive palladium. Therefore, by using the conductive paste of this embodiment, an electrode having high sulfidation resistance and low cost can be formed. In particular, when silver particles are used as metal particles, silver is easily sulfided. By using the conductive paste of this embodiment, disconnection of an electrode using silver as a main material due to sulfidation can be effectively suppressed at low cost.
[0079] For example, when silver particles are used as metal particles, the reason why the sulfidation of silver particles can be suppressed by using surface-treated metal particles (surface-treated silver particles) that have been surface-treated with palladium compounds can be inferred as follows. That is, it can be inferred that the palladium as a surface treatment component forms a uniform alloy layer with the metal particles due to sintering, thereby improving the sulfidation resistance. In the case of a conductive paste of a type that is sintered at a relatively high temperature (e.g., 500 to 900°C), the palladium in the palladium compound exists in the form of a metal particle and a palladium metal alloy layer (a palladium-silver alloy layer when the metal particle is a silver particle) due to sintering. The palladium metal alloy layer is believed to impart high sulfidation resistance to the metal particles. In addition, it is believed that in the case of a thermosetting conductive paste that is heat-cured by heat treatment at a relatively low temperature (e.g., 100 to 200°C), the palladium compound is formed in the form of a thin film on the surface of metal particles such as silver particles, thereby obtaining sulfidation resistance. It should be noted that the content of palladium contained in the surface treatment layer is not very high. Therefore, compared with the case where palladium particles are added separately, the amount of palladium used can be less, so that high sulfidation resistance can be obtained at a low cost. The electrode obtained in this way has high sulfidation resistance and excellent adhesion to the substrate. The same inference can be made about other metal particles other than silver particles. However, the present invention is not limited to this inference.
[0080] By making the conductive particles (A) of the conductive paste of the present embodiment contain given surface-treated metal particles, the migration resistance of the obtained electrode can be improved as an additional effect. The reason why the migration resistance can be improved by using surface-treated metal particles (surface-treated silver particles) surface-treated with palladium compounds can be inferred as follows: by using surface-treated metal particles surface-treated with palladium compounds, the density of the electrode is improved while having the effect of palladium migration resistance. As a result, the migration resistance is improved. However, the present invention is not limited to this inference.
[0081] In the conductive paste of the present embodiment, the content of palladium contained in the surface-treated metal particles is preferably 0.01 parts by weight or more relative to 100 parts by weight of the metal particles, more preferably 0.05 parts by weight or more, particularly preferably 0.08 parts by weight or more, and most preferably 0.2 parts by weight or more. In addition, the content of palladium is preferably 1.0 parts by weight or less relative to 100 parts by weight of the metal particles, more preferably 0.8 parts by weight or less, further preferably 0.6 parts by weight or less, particularly preferably 0.4 parts by weight or less, and most preferably 0.3 parts by weight or less. By making the content of palladium contained in the surface-treated metal particles within the above range, the amount of palladium used is small, and the change in the resistance value of the electrode caused by the sulfidation of the electrode can be reduced at low cost. In addition, the fluidity of the conductive particles is improved when the paste is made, and the leveling property during printing can be further improved. It should be noted that the content of palladium contained in the surface-treated metal particles can be measured by ICP emission spectrometry (high-frequency inductively coupled plasma emission spectrometry).
[0082] The shape of the (A) conductive particles is not particularly limited, and for example, spherical, granular, flaky, and / or scaly surface-treated metal particles can be used.
[0083] The average particle size of the (A) conductive particles is preferably 0.1 μm to 10 μm, more preferably 0.2 μm to 8 μm, further preferably 0.3 μm to 7 μm, and particularly preferably 0.4 to 6 μm. The average particle size referred to here means the volume-based median diameter (D50) obtained by laser diffraction scattering particle size distribution measurement. When the average particle size (D50) of the (A) conductive particles is greater than 10 μm, the sintering property is poor and a dense film cannot be obtained. In addition, when the average particle size (D50) of the (A) conductive particles is less than 0.1 μm, there is a tendency for the dispersibility to deteriorate, and it is difficult to obtain a uniform film when printing the conductive paste.
[0084] The content of (A) conductive particles is 80 parts by weight or more, preferably 83 parts by weight or more, and more preferably 85 parts by weight or more, based on 100 parts by weight of the conductive paste. The upper limit of the content of the conductive particles is not particularly limited, but from the viewpoint of the conductive paste having sufficient printing properties, it is preferably 99.9 parts by weight or less, more preferably 99.5 parts by weight or less, further preferably 99 parts by weight or less, and particularly preferably 95 parts by weight or less, based on 100 parts by weight of the conductive paste.
[0085] <(B)Binder resin>
[0086] The conductive paste of the present embodiment contains (B) a binder resin.
[0087] The (B) binder resin is a substance that connects the (A) conductive particles in the conductive paste. It should be noted that the conductive paste of this embodiment may contain the (C) glass powder described later, or may not contain it. The function of the (B) binder resin contained in the conductive paste of this embodiment is different when the (C) glass powder is contained and when the (C) glass powder is not contained.
[0088] When the conductive paste of the present embodiment includes the glass powder (C), the conductive paste of the present embodiment is applied to a given substrate in a manner to form a given electrode pattern, and fired at a relatively high temperature (e.g., 500 to 900° C.), thereby forming an electrode. In this case, the binder resin (B) is burned out during firing. Therefore, the function of the binder resin (B) in this case is to connect the conductive particles (A) when the conductive paste of the present embodiment is applied to a given substrate in a manner to form a given electrode pattern.
[0089] In the case where the conductive paste of the present embodiment does not contain the (C) glass powder, the conductive paste of the present embodiment is applied to a given substrate in a manner to form a given electrode pattern, and heat-treated at a relatively low temperature (e.g., 100 to 200° C.), thereby forming an electrode. In this case, the (B) binder resin will not burn out during the heat treatment. The function of the (B) binder resin in this case is not only to connect the (A) conductive particles when the conductive paste of the present embodiment is applied to a given substrate in a manner to form a given electrode pattern, but also to connect the (A) conductive particles after the heat treatment, thereby maintaining the shape of the electrode after the heat treatment.
[0090] As the (B) binder resin, for example, cellulose resins such as ethyl cellulose resin and nitrocellulose resin, acrylic resins, alkyd resins, saturated polyester resins, butyral resins, polyvinyl alcohol, and thermoplastic resins such as hydroxypropyl cellulose can be used. These resins can be used alone or in combination of two or more.
[0091] As the (B) binder resin, it is preferable to use at least one selected from cellulose-based resins such as ethyl cellulose resin and nitrocellulose resin, and alkyd resins.
[0092] In the case where the conductive paste of the present embodiment does not contain (C) glass powder, in order to improve the adhesion between the surface-treated metal particles, the conductive paste of the present embodiment may contain an epoxy resin as (B) binder resin. There is no particular limitation on the type of epoxy resin, and known epoxy resins can be used. As epoxy resins, for example, epoxy resins such as bisphenol A type, bisphenol F type, biphenyl type, tetramethylbiphenyl type, cresol novolac type, phenol novolac type, bisphenol A novolac type, dicyclopentadiene phenol condensation type, phenol aralkyl condensation type and glycidylamine type, brominated epoxy resins, alicyclic epoxy resins and aliphatic epoxy resins can be cited. These epoxy resins can be used alone or in combination of two or more. In addition, thermosetting resins other than epoxy resins can also be used for the purpose of improving the adhesion between the surface-treated metal particles. In addition, thermoplastic resins such as polyurethane resins and / or polycarbonate resins can also be used.
[0093] The content of the (B) binder resin is preferably 25 parts by weight or less, more preferably 18 parts by weight or less, further preferably 11 parts by weight or less, and particularly preferably 9 parts by weight or less, relative to 100 parts by weight of the (A) conductive particles. In addition, the lower limit of the content of the (B) binder resin is preferably 0.1 parts by weight, more preferably 0.5 parts by weight, further preferably 1 part by weight, and particularly preferably 1.5 parts by weight. When the content of the (B) binder resin in the conductive paste is within the above range, the coating property of the conductive paste to the substrate (base material) and / or the leveling property of the paste are improved, and an excellent printed shape can be obtained. On the other hand, if the content of the (B) binder resin is greater than the above upper limit range, the amount of the (B) binder resin contained in the applied conductive paste is too much. Therefore, it may not be possible to form electrodes, etc. with high precision.
[0094] <(C)Glass powder>
[0095] The conductive paste of this embodiment may further contain (C) glass frit.
[0096] When the conductive paste of the present embodiment includes the glass powder (C), the conductive paste of the present embodiment is applied to a given substrate in a manner to form a given electrode pattern, and fired at a relatively high temperature (e.g., 500 to 900° C.), thereby forming an electrode. In this case, the binder resin (B) described above is burned out during firing. By connecting the conductive particles (A) with each other using the glass powder (C) contained in the conductive paste, the shape of the electrode after firing can be maintained.
[0097] The glass frit is not particularly limited, but preferably has a softening point of 300° C. or higher, more preferably 400 to 900° C., and even more preferably 500 to 800° C. The softening point of the glass frit can be measured using a thermogravimetric measuring apparatus (eg, TG-DTA2000SA manufactured by BRUKER AXS).
[0098] Examples of (C) glass powder include borosilicate-based and barium borosilicate-based glass powders. In addition, examples of glass powder include bismuth borosilicate-based, alkali metal borosilicate-based, alkaline earth metal borosilicate-based, zinc borosilicate-based, lead borosilicate-based, lead borate-based, lead silicate-based, bismuth borate-based, and zinc borate-based glass powders. Two or more of these glass powders may be mixed and used. From the perspective of environmental considerations, the glass powder is preferably lead-free.
[0099] The glass frit preferably contains at least one selected from ZnO, Bi2O3, BaO, Na2O, CaO, and Al2O3. The glass frit more preferably contains at least one selected from ZnO and Bi2O3.
[0100] When the conductive paste of the present embodiment contains (C) glass frit, the glass frit further preferably contains ZnO. When glass frit containing ZnO (zinc-based glass frit) is used as the glass frit, an electrode with higher sulfidation resistance can be obtained.
[0101] When the conductive paste of the present embodiment contains (C) glass frit, the glass frit further preferably contains Bi 2 O 3. When glass frit (bismuth-based glass frit) containing Bi 2 O 3 is used as the glass frit, the density of the electrode can be improved.
[0102] The average particle size of the glass powder is preferably 0.1 to 20 μm, more preferably 0.2 to 10 μm, and particularly preferably 0.5 to 5 μm. The average particle size here refers to a volume-based median diameter (D50) obtained by laser diffraction scattering particle size distribution measurement.
[0103] When the conductive paste of the present embodiment contains (C) glass powder, the content of (C) glass powder is preferably 0.05 to 10 parts by weight, more preferably 0.5 to 8 parts by weight, further preferably 1 to 6 parts by weight, and particularly preferably 2 to 4 parts by weight relative to 100 parts by weight of the conductive particles (A). When the content of the glass powder is less than this range, the adhesion between the electrode obtained by firing the conductive paste and the substrate (base material) is reduced. When the content of the glass powder is greater than this range, the resistance value of the electrode obtained by firing the conductive paste is high, and the surface of the fired body is covered with a glass component, so the plating property deteriorates. It should be noted that when the content of the glass powder is small, a low-resistance electrode can be obtained. In addition, when the content of the glass powder is large, an electrode with excellent chemical resistance can be obtained. Chemical resistance is a characteristic required because a plating pretreatment is required when a plating film is formed on the surface of the electrode. The plating pretreatment is performed for the purpose of removing contaminants from the surface of the electrode, activating the surface of the electrode, and making it a clean state suitable for plating. The pollutants that should be removed can be roughly divided into organic and inorganic types. The pretreatment process is not a process that uses a single process to remove all pollutants. For example, organic substances are removed by using a process using an alkaline detergent. Inorganic substances are removed by using a process using an acidic detergent. Therefore, the electrode is required to have high chemical resistance.
[0104] When the conductive paste of the present embodiment includes (C) glass powder, the glass powder softens as the temperature rises, and the sintering (firing) of the (A) conductive particles is advanced. When the glass powder content is high, the glass component may be squeezed out to the surface of the fired body. In this case, the surface of the fired body may be covered with the glass component. When the (C) glass powder includes zinc oxide, the Zn component in the glass powder precipitates as ZnO at the crystallization temperature, and thus can contribute to the sulfurization resistance of the (A) conductive particles after firing, similarly to the palladium in the surface-treated metal particles.
[0105] <(D)Additives>
[0106] The conductive paste of the present embodiment may contain a dispersant as the (D) additive. When the conductive paste of the present embodiment contains a dispersant, the dispersibility of the (A) conductive particles in the conductive paste can be improved, and aggregation of the (A) conductive particles can be prevented.
[0107] As the dispersant, a known dispersant can be used. As the dispersant, for example, fatty acid amide, an acid-type low-molecular dispersant, or bismuth oxide (Bi 2 O 3 ) can be used.
[0108] The conductive paste of the present embodiment may contain organic additives and inorganic additives as (D) additives other than the dispersant. As (D) additives, for example, silica fillers, rheology modifiers, and / or pigments may be used.
[0109] By adding an organic additive as the (D) additive to the conductive paste, the printing characteristics of the conductive paste can be improved. By adding a dispersant as the (D) additive to the conductive paste, the dispersibility of the (A) conductive particles and the like can be improved. By adding an inorganic additive as the (D) additive to the conductive paste, the adhesion of the conductive paste after firing can be improved.
[0110] <(E)Solvent>
[0111] The conductive paste of the present embodiment may contain (E) a solvent. Examples of the solvent include alcohols such as methanol, ethanol, and isopropyl alcohol (IPA), organic acids such as ethylene acetate, aromatic hydrocarbons such as toluene and xylene, N-alkylpyrrolidones such as N-methyl-2-pyrrolidone (NMP), amides such as N,N-dimethylformamide (DMF), ketones such as methyl ethyl ketone (MEK), cyclic carbonates such as terpineol (TEL) and diethylene glycol monobutyl ether (butyl carbitol, BC), bis[2-(2-butoxyethoxy)ethyl]adipate, 2,2,4-trimethylpentane-1,3-diol monoisobutyrate (TEXANOL), and water.
[0112] The content of the solvent in the conductive paste of the present embodiment is not particularly limited. For example, the content of the solvent is preferably 1 to 100 parts by weight, more preferably 5 to 60 parts by weight, and even more preferably 8 to 35 parts by weight, based on 100 parts by weight of the (A) conductive particles.
[0113] The viscosity of the conductive paste of the present embodiment varies depending on the viscosity measurement conditions. However, the viscosity was measured using an HB type viscometer (Brookfield) (SC4-14 rotor) at a temperature of 25° C. and a rotation speed of 1 rpm (shear rate of 0.4 sec -1 ) is preferably 100 to 1000 Pa•s, and more preferably 200 to 800 Pa•s. The viscosity of the conductive paste of this embodiment can be adjusted by appropriately controlling the content of the solvent. By adjusting the viscosity of the conductive paste to this range, the coating and / or operability of the conductive paste on the substrate (base material) becomes good, and the conductive paste can be applied to the substrate with a uniform thickness.
[0114] The viscosity of the conductive paste of the present embodiment can also be expressed as a value under conditions different from the above conditions. The viscosity of the conductive paste of the present embodiment can ... -1 ) under the condition of 50-700 Pa•s, and more preferably 100-300 Pa•s. The viscosity of the conductive paste of the present embodiment can be adjusted by appropriately controlling the content of the solvent. By adjusting the viscosity of the conductive paste to this range, the coating property and / or operability of the conductive paste on the substrate (base material) become good, and the conductive paste can be applied to the substrate with a uniform thickness.
[0115] The conductive paste of the present embodiment has a thixotropic index value (TI) of 2.5 or less, more preferably 2.4 or less, as the ratio of the viscosity at a rotation speed of 1 rpm to the viscosity at a rotation speed of 10 rpm, measured by an HB type viscometer at 25°C. The thixotropic index value is the ratio of the viscosity between the measurement conditions where the rotation speed of the viscometer is a ratio of 1:10, and is a value that serves as an indicator of fluidity. If the TI is 2.5 or less, it is preferred because good leveling properties are easily obtained due to moderate fluidity. There is no particular limitation on the lower limit of the TI, but from the perspective of preventing printing expansion and ensuring dimensional stability, it is preferably 1.3 or more.
[0116] <(F)Curing agent>
[0117] The conductive paste of the present embodiment preferably further includes (F) a curing agent. When the conductive paste of the present embodiment includes an epoxy resin as the (B) binder resin, the curing of the epoxy resin can be appropriately controlled by including the (F) curing agent.
[0118] (F) A known curing agent can be used. As the (F) curing agent, it is preferred to include at least one selected from a phenolic curing agent, a cationic polymerization initiator, an imidazole curing agent, and a boron trifluoride compound. As the boron trifluoride compound, boron trifluoride monoethylamine, boron trifluoride piperidine, and boron trifluoride diethyl ether can be cited. As the (F) curing agent, boron trifluoride monoethylamine can be preferably used.
[0119] In the conductive paste of the present embodiment, when the total weight of the conductive particles (A) and the epoxy resin as the binder resin (C) is 100 parts by weight, the conductive paste preferably contains 0.1 to 5 parts by weight of the curing agent (F), more preferably 0.15 to 2 parts by weight, further preferably 0.2 to 1 part by weight, and particularly preferably 0.3 to 0.6 parts by weight. By setting the weight ratio of the curing agent (F) to a given range, the epoxy resin as the binder resin component (B) can be properly cured, and an electrode of a desired shape can be obtained.
[0120] The conductive paste of the present embodiment can be produced by mixing the above-mentioned components using, for example, a pestle, a pot mill, a three-roll mill, a rotary mixer, and / or a twin-screw mixer.
[0121] <Electrode>
[0122] The present embodiment is an electrode obtained by firing or heat-treating the conductive paste of the present embodiment described above.
[0123] When the conductive paste of the present embodiment includes (C) glass powder, the conductive paste of the present embodiment is applied to a given substrate in a manner to form a given electrode pattern, and fired in an air atmosphere at a relatively high temperature (e.g., 500 to 900° C.), thereby forming an electrode. Therefore, the electrode when the conductive paste of the present embodiment includes (C) glass powder can contain (A') conductive particles containing surface-treated metal particles and (C') glass components made of (C) glass powder. After firing, the (A') conductive particles become a sintered state. It should be noted that when the conductive paste of the present embodiment is fired at a relatively high temperature (e.g., 500 to 900° C.), the (B) binder resin and (E) solvent contained in the conductive paste are vaporized or burned during firing. Therefore, the electrode does not substantially contain the (B) binder resin and (E) solvent.
[0124] When the conductive paste of the present embodiment does not contain the (C) glass powder, the conductive paste of the present embodiment is applied to a given substrate in a manner to form a given electrode pattern, and heat-treated at a relatively low temperature (e.g., 100 to 200° C.), thereby forming an electrode. Therefore, the electrode of the present embodiment when the conductive paste of the present embodiment does not contain the (C) glass powder can contain the (A') conductive particles containing surface-treated metal particles and the (B') binder component made of the (B) binder resin. The (A') conductive particles are connected via the (B') binder component.
[0125] Since the surface-treated metal particles contained in the conductive paste of the present embodiment are surface-treated with a palladium compound, the electrode of the present embodiment contains palladium. The electrode of the present embodiment preferably contains 0.01 to 10% by weight of palladium, more preferably 0.05 to 5% by weight of palladium, further preferably 0.07 to 1% by weight of palladium, and particularly preferably 0.08 to 0.5% by weight of palladium. It should be noted that when the conductive paste of the present embodiment contains (C) glass powder, the electrode of the present embodiment may contain palladium derived from the (C) glass powder. By making the electrode of the present embodiment contain a given amount of palladium, the electrode of the present embodiment can have high resistance to sulfidation. It should be noted that the palladium content in the electrode can be measured by elemental analysis based on EDS (Energy Dispersive X-ray Spectroscopy).
[0126] When the conductive paste of the present embodiment includes the glass frit (C), the electrode of the present embodiment may include zinc (zinc oxide) derived from the glass frit (C). When the electrode of the present embodiment includes zinc in addition to palladium, high sulfidation resistance can be obtained.
[0127] The sheet resistance of the thin film used as the electrode of this embodiment varies depending on the film thickness, but can be generally set to about 10 mΩ / □ (10 mΩ / square) or less. Therefore, it can be preferably used to form an electrode requiring low resistance.
[0128] Next, a method for forming an electrode on a substrate (base material) using the conductive paste of the present embodiment is described. First, the conductive paste is applied to the substrate. The conductive paste can be applied by any method, for example, by glue dripping, glue jetting, stencil printing, screen printing, pin transfer, or stamping.
[0129] In the case where the conductive paste of the present embodiment includes (C) glass powder, after the conductive paste is applied to the substrate, it is dried as needed, and the substrate is placed in a firing furnace or the like. Thereafter, the conductive paste applied to the substrate is fired at 500 to 900°C, more preferably at 600 to 880°C, and further preferably at 700 to 870°C. A specific example of the firing temperature is 850°C. As a result, the solvent component contained in the conductive paste evaporates below 300°C, and the resin component is burned at 400°C to 600°C to form a fired body (electrode) of the conductive paste. In addition, the organic component contained in the surface-treated metal particles disappears due to firing in an air atmosphere, and the palladium in the palladium compound exists on the surface of the metal particles in the form of a palladium metal alloy layer (a palladium-silver alloy layer when the metal particles are silver particles). The palladium metal alloy layer on the surface of the metal particles is believed to impart high sulfidation resistance to the metal particles. Therefore, by making the metal particles include a surface treatment layer of a thin film containing a palladium compound, high sulfidation resistance can be obtained. In addition, the content of palladium contained in the surface treatment layer is not very high. Therefore, compared with the case of adding palladium particles separately, the amount of palladium used can be less, so that high sulfidation resistance can be obtained at low cost. The electrode obtained in this way has high sulfidation resistance and excellent adhesion to the substrate.
[0130] In the case where the conductive paste of the present embodiment does not contain (C) glass powder, after the conductive paste is applied to the substrate, the substrate is placed in a heat treatment furnace or the like. Thereafter, the conductive paste applied to the substrate is heat treated at 100 to 200°C, more preferably at 150 to 200°C. The heat treatment time is preferably 20 to 90 minutes, more preferably 30 to 60 minutes. A specific example of the heat treatment conditions is 150°C and 60 minutes. Thus, the solvent component contained in the conductive paste is dried, and the conductive paste is thermally cured, thereby forming a cured body (electrode) of the conductive paste. The electrode obtained in this way has high resistance to sulfidation and excellent adhesion to the substrate.
[0131] When the conductive paste of the present embodiment does not contain the (C) glass frit, an example of a particularly preferred content of palladium contained in the electrode of the present embodiment is 0.2 to 0.5% by weight.
[0132] The conductive paste of the present embodiment has excellent printing properties as a coating, and has high coating smoothness when the electrode is made by the method described above. If the smoothness is high, the surface area of the coating becomes smaller, and the part affected by sulfur in the atmosphere becomes less, so it is advantageous in terms of sulfur resistance. In addition, if the coating is smooth, the accuracy of the coating is improved when the electrode is further plated with nickel, etc. Therefore, the smoothness of the coating helps to form a fine electrode. In this specification, the smoothness of the coating is evaluated by surface roughness Ra. The so-called surface roughness Ra refers to the center line average roughness (arithmetic mean roughness), which means the value measured using a surface roughness-shape measuring machine in accordance with JIS B 0601 (1994). The arithmetic mean roughness (Ra) of the electrode surface is preferably less than 0.5μm, more preferably less than 0.46μm, and particularly preferably less than 0.43μm.
[0133] In addition, the electrode obtained as described above using the conductive paste of this embodiment can have an additional advantage of improved migration resistance. This additional advantage can be obtained both when the conductive paste contains (C) glass powder and when it does not contain (C) glass powder. However, it is considered that this advantage is not necessarily an essential effect of the conductive paste of this embodiment, but is an advantage.
[0134] <Electronic components or electronic equipment>
[0135] The present embodiment is an electronic component or electronic device having the above-mentioned electrode. In this specification, the so-called electronic component means a component used in electronic devices such as chip resistors and substrate circuits. In this specification, the so-called electronic component means a component that works electronically, specifically, it can be a component that operates below 48V of direct current. In this specification, the so-called electronic device means a device including an electronic component having an electrode of this embodiment.
[0136] The conductive paste of the present embodiment can be used for forming circuits of electronic components or electronic devices, forming electrodes, and bonding electronic components to a substrate (base material) of a device (eg, semiconductor chip).
[0137] The conductive paste of this embodiment can be preferably used for forming electrodes of a chip resistor. Figure 1An example of the cross-sectional structure of the chip resistor 100 of the present embodiment is shown in FIG. The chip resistor 100 may have a rectangular alumina substrate 102 and a resistor 104 and a lead electrode 106 arranged on the surface of the alumina substrate 102. The lead electrode 106 is an electrode for extracting electricity from the resistor 104. In addition, a lower surface electrode 108 for mounting the chip resistor 100 on the substrate may be arranged on the lower surface of the alumina substrate 102. In addition, a connecting electrode 110 for connecting the lead electrode 106 and the lower surface electrode 108 may be arranged on the end surface of the alumina substrate 102. Using the conductive paste of the present embodiment, at least one of the lead electrode 106, the lower surface electrode 108, and the connecting electrode 110 may be formed. It is particularly preferred to form the lead electrode 106 using the conductive paste of the present embodiment. It should be noted that a nickel plated film 112 and a tin plated film 114 may be disposed on the upper surfaces (surfaces on the opposite side to the alumina substrate 102 ) of the extraction electrode 106 , the lower surface electrode 108 , and the connection electrode 110 .
[0138] The electrodes of this embodiment are not limited to the electrodes of chip resistors. The electrodes formed using the conductive paste of this embodiment can be used as electrodes of various electronic components. As electronic components, passive components (such as chip resistors, capacitors, resistors and inductors, etc.), circuit substrates (for example, circuit substrates on which a given circuit (electrode or wiring) is formed on a substrate such as an aluminum oxide substrate, an aluminum nitride substrate and a glass substrate), solar cell units and electromagnetic wave shielding, etc. can be cited. The conductive paste of this embodiment can be used to form the electrodes and / or wiring of these electronic components. As electronic devices including electronic components having electrodes of this embodiment, electronic devices including semiconductor devices, solar power generation modules and circuit substrates can be cited.
[0139] The conductive paste of this embodiment can be used as a chip pasting material for mounting a semiconductor chip in a semiconductor device. In the case where the semiconductor device is a power semiconductor device, it can be used as a solder for mounting a power semiconductor chip. The conductive paste of this embodiment can be used as an electrode of a solar cell. The conductive paste of this embodiment can be used as a conductive adhesive. In addition, the conductive paste of this embodiment is not limited to the formation of terminal electrodes of chip resistors, and can also be suitably used as a conductive paste for terminal electrodes of passive components such as MLCC and chip inductors.
[0140] By using the conductive paste of this embodiment, it is possible to form an electrode having high sulfurization resistance, low resistance, and low cost. Therefore, by using the conductive paste of this embodiment, it is possible to obtain electronic components such as chip resistors having electrodes with high reliability at low cost.
[0141] Example
[0142] Hereinafter, the present invention will be specifically described using Examples, but the present invention is not limited to these Examples.
[0143] [Preparation of conductive paste]
[0144] The following (A) to (F) components were mixed in the proportions shown in Tables 1 to 3 to prepare a conductive paste. It should be noted that the proportions of the components shown in Tables 1 to 3 are all expressed in parts by weight. In Tables 1 to 3, the weight of the conductive particles (A) (the total weight of the metal particles and the surface-treated metal particles) is set to 100 parts by weight. In addition, the average particle size refers to the volume-based median diameter (D50) obtained by laser diffraction scattering particle size distribution measurement method.
[0145] (A) Conductive particles
[0146] Table 4 shows metal particles a1 to a4 and surface-treated metal particles A1 to A6 used as (A) conductive particles ((A) component) of examples and comparative examples. Metal particles a1 and a2 are silver particles, and metal particle a4 is a palladium particle. Metal particles a1 to a4 are not surface-treated. Regarding surface-treated metal particles A1 to A6, a palladium soap solvent (surface treatment agent) obtained by dispersing a palladium compound in a solvent is attached to the surface of the metal particles, which are silver particles as metal particles, and the solvent is removed by a drying process, thereby performing surface treatment. Therefore, the surface-treated metal particles A1 to A6 have a surface-treated layer containing a palladium compound. In the "Pd content" column of Table 4, the weight ratio of palladium contained in the surface-treated layer relative to the weight of the surface-treated metal particles A1 to A6 is shown in units of weight %. The weight ratio of palladium in the surface-treated metal particles is measured by ICP emission spectrometry (high-frequency inductively coupled plasma emission spectrometry).
[0147] The surface treatment of the silver particles with the palladium compound is performed as follows. That is, the surface treatment of the silver particles with the palladium compound is performed using a palladium soap solvent (surface treatment agent) containing a palladium compound, an organic substance for dispersing the palladium compound, and a solvent. The palladium soap solvent (surface treatment agent) is attached to the surface of the silver particles, and the solvent is removed by a drying process, thereby performing the surface treatment. Palladium chloride is used as the palladium compound. In addition, oleic acid is used as a solvent contained in the surface treatment agent for the silver particles. A surface treatment layer is formed on the surface-treated metal particles A1 to A6 as described above.
[0148] (B) Binder resin
[0149] (B) Binder resins (resins B1 to B5) used in Examples and Comparative Examples are shown in Table 5. Tables 1 to 3 show the blending amounts of resins B1 to B5 in the conductive pastes of Examples and Comparative Examples.
[0150] (C) Glass powder
[0151] The (C) glass frits (C1 to C5) used in Examples and Comparative Examples are shown in Table 6. Tables 1 to 3 show the blending amounts of the glass frits C1 to C5 in the conductive pastes of Examples and Comparative Examples.
[0152] (D) Additives
[0153] Table 7 shows the (D) additives (additives D1 to D3) used in the examples and comparative examples. Tables 1 to 3 show the amounts of additives D1 to D3 in the conductive pastes of the examples and comparative examples. Additive D1 is an organic additive. By adding additive D1, the printing characteristics of the conductive paste can be improved. Additive D2 is a dispersant. By adding additive D2, the dispersibility of (A) conductive particles, etc. can be improved. Additive D3 is an inorganic additive. By adding additive D3, the adhesion of the conductive paste after firing can be improved.
[0154] (E) Solvent
[0155] The (E) solvents (solvents E1 to E3) used in Examples and Comparative Examples are shown in Table 8. Tables 1 to 3 show the blending amounts of the solvents E1 to E3 in the conductive pastes of Examples and Comparative Examples.
[0156] (F) Curing agent
[0157] In the conductive pastes of Examples and Comparative Examples, boron trifluoride monoethylamine (Sterachemifa Co., Ltd., model: BF3MEA) was used as (F) curing agent F1. Tables 1 to 3 show the blending amounts of curing agent F1 in the conductive pastes of Examples and Comparative Examples.
[0158] [Preparation of Test Specimen 50 for Sulfurization Resistance Test]
[0159] Figure 2 A schematic diagram of a test piece 50 for the sulfidation resistance test is shown in . Using a conductive paste containing (C) glass frit, test pieces 50 for the sulfidation resistance test of Examples 1 to 16 and Comparative Examples 1 to 5 were prepared by the following procedure.
[0160] First, on an alumina substrate 52 (purity 96%) for sulfurization resistance test of 20 mm×20 mm×1 mm (t), a screen printing was performed to form a Figure 2The conductive paste was applied in the manner of a zigzag printed pattern 54 for the sulfidation resistance test shown. The length between the two ends 54a and 54b of the printed pattern 54 for the sulfidation resistance test was 71 mm, and the width of the printed pattern 54 for the sulfidation resistance test was 1 mm. In order to form the printed pattern 54 for the sulfidation resistance test of the conductive paste, a 325-mesh screen (emulsion thickness 5 μm) made of stainless steel was used for screen printing. Then, the printed pattern 54 for the sulfidation resistance test of the conductive paste was dried at 150°C for 10 minutes using an intermittent hot air dryer. After the printed pattern 54 for the sulfidation resistance test of the conductive paste was dried, the printed pattern 54 for the sulfidation resistance test was fired using a belt-type firing furnace. The firing temperature was maintained at 850°C for 10 minutes. The total time from entering the firing furnace to taking it out was 60 minutes. The test pieces 50 of Examples 1 to 16 and Comparative Examples 1 to 5 were prepared as described above.
[0161] In Examples 17 to 19 using the conductive paste not containing the glass powder (C), the conductive paste of Examples 17 to 19 was used in the same manner as in Examples 1 to 16 and Comparative Examples 1 to 5, and a zigzag sulfidation resistance test printed pattern 54 having a width of 1 mm and a length of 71 mm was formed by screen printing on an alumina substrate 52 for sulfidation resistance test (purity 96%) of 20 mm×20 mm×1 mm (t) (see Figure 2 ). Then, the printed pattern 54 for the sulfurization resistance test of the conductive paste was heat-treated at 150° C. for 10 minutes using an intermittent hot air dryer, thereby curing the printed pattern 54 for the sulfurization resistance test. Test pieces 50 of Examples 17 to 19 were prepared as described above.
[0162] [Sulfurization resistance test method]
[0163] First, the resistance (initial resistance) between the two ends 54a and 54b of the printed pattern 54 of the test piece of the embodiment and the comparative example is measured. Then, a dish (height 18mm, diameter 86mm) to which 10g of sulfur powder is added in a flat manner is placed at the bottom of a glass desiccator (height 420mm, diameter 300mm), and the test piece of the embodiment and the comparative example is placed on the shelf. The desiccator is kept in a constant temperature bath at 60°C for 150 hours to vulcanize the test piece. Then, the resistance after vulcanization is measured. In the "Resistance Value Change Ratio (Vulcanization Resistance Test)" column of Tables 1 to 3, the resistance value change ratio of the resistance after vulcanization relative to the initial resistance of the embodiment and the comparative example is expressed in percentage units. The resistance value change ratio can be expressed by the following formula.
[0164] Resistance change ratio = (resistance after vulcanization - initial resistance) / initial resistance
[0165] [Preparation of test pieces for adhesive strength test]
[0166] Using the prepared conductive paste, test pieces of Examples 1 to 16 and Comparative Examples 1 to 5 containing (C) glass powder were prepared using the following steps. First, the conductive paste was applied to an alumina substrate (purity 96%) of 20 mm × 20 mm × 1 mm (t) by screen printing. Thus, 25 (5 × 5) bonding strength test patterns consisting of square pads with a side length of 1.5 mm were formed on the alumina substrate. In order to form the bonding strength test pattern of the conductive paste, screen printing was performed using a 325-mesh stainless steel screen (emulsion thickness 5 μm).
[0167] Then, the conductive paste was dried at 150°C for 10 minutes using an intermittent hot air dryer. After the conductive paste bonding strength test pattern was dried, the conductive paste bonding strength test pattern was fired using a belt-type firing furnace. The firing temperature was maintained at 850°C for 10 minutes. The total time from entering the firing furnace to taking it out was 60 minutes. Test pieces of Examples 1 to 16 and Comparative Examples 1 to 5 were prepared as described above.
[0168] Then, the bonding strength test pattern was plated with Ni / Au. Then, after the solder (M705 manufactured by Senju Metal Industry Co., Ltd., a Sn alloy containing 3.0 wt% Sn-Ag and 0.5 wt% Cu) was attached to the bonding strength test pattern at 260°C for 3 seconds, the Sn-plated soft copper wire (diameter 0.8 mm) was brazed to the bonding strength test pattern. It should be noted that among the 5×5 bonding strength test patterns on the alumina substrate, 5 Sn-plated soft copper wires were brazed one each in the 2nd column, totaling 5 Sn-plated soft copper wires, and 5 Sn-plated soft copper wires were brazed one each in the 4th column, totaling 5 Sn-plated soft copper wires, thereby brazing the Sn-plated soft copper wires. A total of 10 Sn-plated soft copper wires were brazed, and the tensile bonding strength of the lead was measured using a strength tester. Specifically, the alumina substrate was placed vertically at an angle of 90 degrees relative to the strength tester so that the pattern for the adhesive strength test was on the upper surface, and the lead was pulled vertically upward relative to the alumina substrate to measure the tensile adhesive strength. The force (N) when the lead was peeled off was defined as the tensile adhesive strength.
[0169] As with the test pieces of Examples 1 to 16 and Comparative Examples 1 to 5, the conductive paste prepared as Examples 17 to 19 was applied by screen printing on an alumina substrate (purity 96%) of 20 mm × 20 mm × 1 mm (t). Thus, 25 (5 × 5) bonding strength test patterns consisting of square pad shapes with a side length of 1.5 mm were formed on the alumina substrate. Then, the conductive paste was heat-treated at 150°C for 10 minutes using a hot air dryer, thereby curing the bonding strength test pattern of the conductive paste. Test pieces of Examples 17 to 19 were prepared as described above. Then, as with Examples 1 to 16 and Comparative Examples 1 to 5, the bonding strength test patterns of Examples 17 to 19 were plated with Ni / Au. Then, similarly to the test pieces of Examples 1 to 16 and Comparative Examples 1 to 5, Sn-plated soft copper wires (leads) were soldered to the bonding strength test patterns, and the tensile bonding strength of the leads was measured using a strength tester.
[0170] The results of the adhesive strength test were obtained by measuring the tensile adhesive strength of 10 test pieces of each example and each comparative example. The "Adhesive Strength (N)" column in Tables 1 to 3 shows the average value of the tensile adhesive strength of the 10 test pieces of each example and each comparative example measured as described above.
[0171] [Migration resistance test]
[0172] Figure 3 2 shows an optical microscope photograph of test printed patterns 64a and 64b of an example of a test piece 60 for the migration resistance test. Using the prepared conductive paste, test pieces 60 for the migration resistance test of Examples 1, 3, 17 to 19, and Comparative Example 1 were prepared by the following procedure.
[0173] The test pieces 60 for the migration resistance test of Examples 1, 3 and Comparative Example 1 were prepared by the following steps. First, on an alumina substrate 62 (purity 96%) for the migration resistance test of 110 mm×20 mm×0.8 mm (t), a screen printing method was used. Figure 3 and as Figure 3 Enlarged photo of Figure 4As shown, the conductive paste is applied in a staggered manner with two comb-shaped migration test print patterns 64a and 64b. The migration test print pattern 64a is connected to the first electrode 66a, and the migration test print pattern 64b is connected to the second electrode 66b. The printing width L of the migration test print patterns 64a and 64b is 200 μm, and the gap S between the migration test print patterns 64a and 64b is 200 μm. In order to form the migration test print patterns 64a and 64b of the conductive paste and the electrodes 66a and 66b, a 400-mesh stainless steel screen (emulsion thickness 10 μm) is used for screen printing. Then, the migration test print patterns 64a and 64b of the conductive paste and the electrodes 66a and 66b are dried at 150°C for 10 minutes using an intermittent hot air dryer. After drying the printed patterns 64a, 64b and electrodes 66a, 66b of the conductive paste for migration resistance test, the printed patterns 64a, 64b and electrodes 66a, 66b for migration resistance test were fired using a belt-type firing furnace. The firing temperature was maintained at 850°C for 10 minutes. The total time from entering the firing furnace to taking it out was 60 minutes. The thickness of the printed patterns 64a, 64b and electrodes 66a, 66b for migration resistance test after firing was 10 to 20 μm. As described above, the test pieces 60 for migration resistance test of Examples 1 to 16 and Comparative Examples 1 to 5 were prepared.
[0174] The test pieces 60 for the migration resistance test of Examples 17 to 19 were prepared by the following steps. First, similarly to the test pieces 60 of Examples 1, 3 and Comparative Example 1, a 110 mm × 20 mm × 0.8 mm (t) alumina substrate 62 for migration resistance test (purity 96%) was screen printed. Figure 3 and Figure 4 As shown in FIG. 1 , the conductive paste was applied in a staggered manner with two comb-shaped printed patterns 64a and 64b for the migration resistance test. Then, the conductive paste was heat-treated at 200° C. for 30 minutes using a hot air dryer to cure the pattern for the adhesive strength test of the conductive paste. Test pieces for the migration resistance test of Examples 17 to 19 were prepared as described above.
[0175] The migration resistance of the printed patterns 64a and 64b for the migration resistance test of the test piece 60 of Examples 1, 3, 17 to 19 and Comparative Example 1 was measured by the following procedure. Figure 3As shown, a voltage (40V) is applied between the first electrode 66a and the second electrode 66b of the two printed patterns 64a and 64b for the migration resistance test. The insulation resistance value between the first electrode 66a and the second electrode 66b is measured in a state of being stored in an environment of a temperature of 85°C and a humidity of 85%. The insulation resistance value is calculated based on the measured value of the current flowing between the first electrode 66a and the second electrode 66b and the applied voltage of 40V. The test piece 60 to which the applied voltage of 40V is applied is maintained in an environment of a temperature of 85°C and a humidity of 85% for a maximum of 487 hours. Table 9 shows the results of the migration resistance test. The insulation resistance value of all samples before the test was 10 7 Ω or more. The insulation resistance value will be 10 within 10 hours. 6 The test pieces with an insulation resistance value of less than 60 Ω were judged as defective and recorded as "defective" in Table 9. 6 The test piece 60 with an insulation resistance of less than 10Ω was judged to be usable in some applications because it was excellent in migration resistance to a certain extent, and was recorded as "usable" in Table 9. 6 The test piece 60 with a value of Ω or less was judged to be excellent in migration resistance and was recorded as "good" in Table 9.
[0176] Figure 7 The time change of the insulation resistance value of Example 1, Example 3 and Comparative Example 1 during the migration resistance test is shown in Table 9. The insulation resistance value of the test piece 60 of Example 3 which was judged to be excellent in migration resistance (recorded as "good" in Table 9) did not drop to 10 even after 480 hours. 6 Ω or less. The test piece 60 of Example 1, which was judged to be usable in some applications due to its excellent migration resistance to a certain extent (described as "usable" in Table 9), did not decrease in insulation resistance to 10 even after 80 hours. 6 The test piece 60 of Comparative Example 1 judged to have poor migration resistance (referred to as "poor" in Table 9) had an insulation resistance value of 10 within 10 hours. 6 Ω or less.
[0177] [Solder heat resistance test]
[0178] Using the prepared conductive paste, test pieces for solder heat resistance tests of Examples 1 to 16 and Comparative Examples 1 to 5 containing (C) glass frit were prepared by the following procedure.
[0179] First, a conductive paste was applied by screen printing on an alumina substrate (purity 96%) of 20 mm × 20 mm × 1 mm (t). Thus, 25 (5 × 5) bonding strength test patterns consisting of square pads with a side length of 1.5 mm were formed on the alumina substrate. In order to form the bonding strength test pattern of the conductive paste, screen printing was performed using a 325-mesh stainless steel screen (emulsion thickness 5 μm).
[0180] Then, the conductive paste was dried at 150°C for 10 minutes using an intermittent hot air dryer. After the conductive paste bonding strength test pattern was dried, the conductive paste bonding strength test pattern was fired using a belt-type firing furnace. The firing temperature was maintained at 850°C for 10 minutes. The total time from entering the firing furnace to taking it out was 60 minutes. Test pieces of Examples 1 to 16 and Comparative Examples 1 to 5 were prepared as described above.
[0181] Test pieces for the solder heat resistance test of Examples 17 to 19 were prepared using a conductive paste not containing the (C) glass frit, similarly to the test pieces for the solder heat resistance test of Examples 1 to 16 and Comparative Examples 1 to 5. However, in the case of the test pieces of Examples 17 to 19, instead of drying and firing the pattern for the adhesive strength test of the conductive paste, the conductive paste was heat-treated at 150° C. for 10 minutes using a hot air dryer, thereby curing the pattern for the adhesive strength test of the conductive paste.
[0182] Then, the test piece was immersed for 10 seconds in a solder bath (solder temperature: 260° C.) containing solder (M705 manufactured by Senju Metal Industry Co., Ltd., a Sn alloy containing 3.0 wt % Sn—Ag and 0.5 wt % Cu).
[0183] After dipping the test piece in the solder tank, the test piece was taken out, and the test piece in which 95% or more of the electrode remained was judged as a test piece that passed the solder heat resistance test. In the "Solder Heat Resistance" column of Table 9, if the solder heat resistance test was passed, it was recorded as "good", and if the solder heat resistance test was unqualified, it was recorded as "bad".
[0184] [Surface and cross-sectional observation using SEM and cross-sectional observation using EDS analysis]
[0185] Figure 5 : shows a SEM photograph taken with a scanning electron microscope (SEM) at a magnification of 5000 times of the surface of a test piece produced under the same conditions as the test piece 50 of the sulfurization resistance test of Example 3 having a smaller resistance value change ratio. Figure 6: shows an SEM photograph taken at a magnification of 5000 times of the surface of a test piece produced under the same conditions as the test piece 50 of the sulfurization resistance test of Comparative Example 1, in which the resistance value change ratio is large. It should be noted that, as in the case of the sulfurization resistance test, the test piece was stored in a sulfur atmosphere (60° C.) for 150 hours and then observed by SEM.
[0186] [evaluate]
[0187] As is clear from the results shown in Tables 1 to 3, the resistance value change ratio of the electrode pattern obtained by firing the conductive pastes of Examples 1 to 19 was 65.0% or less (Example 11), which is a relatively low value. In contrast, the resistance value change ratio of the electrode pattern obtained by firing the conductive pastes of Comparative Examples 1 to 5 was 140% or more (Comparative Example 5). Therefore, it can be said that the electrode pattern obtained by firing the conductive pastes of Examples 1 to 19 has excellent sulfurization resistance.
[0188] As is clear from the results shown in Tables 1 to 3, the tensile bonding strength of the bonding strength test pattern obtained by firing the conductive pastes of Examples 1 to 19 is in the range of 13.2N (Example 17) to 17.8N (Examples 11 and 15), and a high tensile bonding strength can be obtained. On the other hand, the tensile bonding strength of the electrode pattern obtained by firing the conductive pastes of Comparative Examples 1 to 4 is in the range of 14.2N (Comparative Example 4) to 15.2N (Comparative Examples 1 to 3), which is a range without problems as far as tensile bonding strength is concerned. In addition, the tensile bonding strength of the electrode pattern obtained by firing the conductive paste of Comparative Example 5 is 7.1N. It can be considered that the conductive paste of Comparative Example 5 has poor sintering properties compared with the other Examples and Comparative Examples, so the tensile bonding strength is a low value.
[0189] As can be clearly seen from the results shown in Tables 1 to 3, the results of the solder heat resistance test of the electrode patterns obtained by firing the conductive pastes of Examples 1 to 19 were all qualified ("good"). On the other hand, the results of the solder heat resistance test of the electrode patterns obtained by firing the conductive pastes of Comparative Examples 1 to 4 were unqualified ("bad"). It should be noted that the result of the solder heat resistance test of the electrode pattern obtained by firing the conductive paste of Comparative Example 5 was qualified ("good"). Based on the above results, it can be said that the solder heat resistance of the electrode patterns obtained by firing the conductive pastes of Examples 1 to 19 is excellent.
[0190] As is apparent from the results shown in Table 9, the electrodes of Examples 1, 3, and 17 to 19 of the present embodiment are superior to Comparative Example 1 in migration resistance.
[0191] Compare Figure 5 The embodiment 3 shown is Figure 6 As can be understood from the SEM photograph of Comparative Example 1 shown, in Comparative Example 1, larger crystals of silver sulfide 20 are formed due to sulfidation than in Example 3. The same trend is observed for the other Examples and Comparative Examples. Therefore, it can be said that the electrode of the Example of this embodiment has higher sulfidation resistance than the Comparative Example. In addition, the Pd content in the depth direction of the sample of Example 3 was measured by X-ray photoelectron spectroscopy (XPS), and as a result, a portion with a Pd content of about 30 atomic % was confirmed at a depth of 80 nm. This result suggests that, at least in the sample of Example 3, the sulfidation resistance of the electrode is improved by forming a silver-palladium alloy layer on the surface of the electrode.
[0192]
[0193]
[0194]
[0195]
[0196]
[0197]
[0198]
[0199]
[0200]
[0201] <Examples 20 to 32, Comparative Examples 6 to 7: Evaluation of coating film smoothness>
[0202] A conductive paste was prepared in the same manner as in Example 1 using the formulation shown in Table 10. The viscosity of the obtained conductive paste was measured using an HB type viscometer (manufactured by Brookfield) (SC4-14 rotor) at a temperature of 25°C and 1 rpm or 10 rpm to determine the TI value. Then, the conductive paste of each embodiment and comparative example was applied to a slide glass in a pattern of 10 mm in width and 50 mm in length to a thickness of about 0.05 mm, and fired at 500°C for 20 minutes to form a conductive film having a film thickness of 0.2 μm after firing. The surface roughness Ra of the obtained conductive film was measured using a surface roughness-shape measuring machine (manufactured by Tokyo Seimitsu Co., Ltd., SURFCOM 1500SD2-12) in accordance with JIS B 0601 (1994). When the surface roughness Ra is less than 0.4 μm, it is considered to be particularly excellent (○), when it is 0.4 to 0.5 μm, it is considered to be practically without problems (△), and when it is greater than 0.5 μm, it is evaluated as a rough surface (×). The formulations and measurement results of each example and comparative example are shown together with the measurement results of the sulfurization resistance in Table 10. It should be noted that the sulfurization resistance test was carried out by the same method as in Examples 1 to 19 and Comparative Examples 1 to 5.
[0203]
[0204] [evaluate]
[0205] As is clear from the results shown in Table 10, the conductive paste of this embodiment has excellent sulfidation resistance and a small TI value, so it has high fluidity, improved leveling, and excellent printing characteristics. In addition, the Ra value is small, and a smooth coating film can be formed. The stereomicroscope images of the conductive films of Example 22 and Comparative Example 6 are shown in FIG. Figure 8 , 9 In Example 22, a flat surface was observed, but in Comparative Example 6, grid marks were confirmed. These results show that the conductive paste of the present embodiment is particularly excellent as a paste for forming a high-definition electrode pattern.
[0206] Description of Reference Numerals
[0207] 50 Test piece for sulfur resistance test, 52 Alumina substrate for sulfur resistance test, 54 Printed pattern for sulfur resistance test, 54a, 54b End of printed pattern for sulfur resistance test, 60 Test piece for migration resistance test, 62 Alumina substrate for migration resistance test, 64a, 64b Printed pattern for migration resistance test, 66a First electrode, 66b Second electrode, 100 Chip resistor, 102 Alumina substrate, 104 Resistor, 106 Lead electrode, 108 Lower surface electrode, 110 Connection electrode, 112 Nickel plating film, 114 Tin plating film.
Claims
1. A conductive paste comprising (A) conductive particles and (B) a binder resin, The conductive particles (A) described above include metal particles and a surface treatment layer containing a palladium compound and disposed on at least a portion of the surface of the metal particles. The conductive particles (A) are contained in an amount of 80 parts by weight or more based on 100 parts by weight of the conductive paste. 2 . The conductive paste according to claim 1 , wherein the viscosity thereof measured by an HB type viscometer at 25° C. and 10 rpm is in the range of 50 Pa·s to 700 Pa·s. 3 . The conductive paste according to claim 1 , wherein the thixotropic index value TI, which is a ratio of the viscosity at a rotation speed of 1 rpm to the viscosity at a rotation speed of 10 rpm, measured at 25° C. using an HB type viscometer, is 2.5 or less.
4. The conductive paste according to any one of claims 1 to 3, wherein The average particle size D50 of the (A) conductive particles is 0.1 μm to 10 μm.
5. The conductive paste according to any one of claims 1 to 4, wherein The metal particles contain 50 wt % or more of silver.
6. The conductive paste according to any one of claims 1 to 5, wherein The content of the palladium compound in the surface treatment layer is 0.01 to 1.0 parts by weight based on 100 parts by weight of the conductive particles.
7. The conductive paste according to claim 6, wherein The content of the palladium compound in the surface treatment layer is 0.2 to 0.4 parts by weight based on 100 parts by weight of the conductive particles.
8. The conductive paste according to any one of claims 1 to 7, wherein The surface treatment layer further comprises an organic matter. 9 . An electrode obtained by firing or heat-treating the conductive paste according to claim 1 . 10 . The electrode according to claim 9 , wherein the electrode surface has an arithmetic mean roughness Ra of 0.5 μm or less as measured in accordance with JIS B 0601 (1994). 11 . An electronic component or electronic device comprising the electrode according to claim 9 or 10.
Citation Information
Patent Citations
Paste for forming electrode on chip resistor
JP1995335402A
Conductive silver paste and electromagnetic wave shielding member using it
JP2005294254A
Electroconductive paste, electrode and chip resistor
WO2021145269A1